Core Blighty? How Journalists Define Themselves Through Metaphor: British Journalism Review 2011–2014. (2nd October 2016) - Conboy, Martin; Tang, Minyao
Abstract : Journalism has long relied on certain core metaphors in order to express its claims to social and political usefulness. The deployment of metaphors to describe a practice that in contrast asserts its truth-telling and plain prose style is in itself interesting. Since metaphor acts as a powerful indicator of presuppositions it can be used to reify complex public discourses, reducing them to common-sense thinking. This paper explores what metaphors have been used in association with journalism in the pages of the British Journalism Review since the closure of the News of the World . Do metaphorical articulations of the current role and image of journalism demonstrate an awareness among journalists of changes in its values or do they rather tend to reinforce more traditional attitudes to a practice under threat? Post-Leveson what can the patterning of such figurative language across articles by a wide range of prominent journalists in the United Kingdom tell us about the values and aspirations of journalists in a time when journalism is under intense scrutiny?